Assessing the Economic Impact of IT-Driven Smart Healthcare Systems in Nigeria - Jamiu Adeniyi Yusuf; Adenegan Micheal Adeyinka; Muhammed Jamiu Abdulrazaq; Gogo Helen Kolo (Indonesian Journal of Health Research and Development, 2025)
Background: To raise service delivery and lower costs, the healthcare industry is increasingly embracing smart technologies. Central to this revolution are wearable devices, telemedicine, and electronic health records (EHRs). To guide investment and policy decisions, it is nevertheless necessary to grasp their true economic effect on healthcare systems.  Aims: This study seeks to assess the economic consequences of IT-driven smart healthcare technologies particularly EHRs, telemedicine, and wearable devices—on healthcare costs, operational efficiency, and health outcomes. It centers on the economic sustainability of the healthcare industry facilitated by these technologies.Methods: The study examines the economic effects of these innovations using econometric modeling and cost-benefit analysis. Data were evaluated to assess their effects on decreased hospital readmissions, efficiency gains, and cost savings.  Result: The results indicate that telemedicine and wearable devices come next after EHRs produce the most significant cost savings. These technologies enhance operational efficiency and lower hospital readmission rates as well, therefore positively impacting both healthcare delivery and economic outcomes.  Conclusion: In conclusion, smart healthcare systems provide quantifiable financial advantages. Their acceptance results in less expensive healthcare and more effective service delivery. Among the instruments examined, EHRs exhibit the most influence, followed by wearable technologies and telemedicine. Policymakers and healthcare professionals should keep investing purposefully in these intelligent technologies. To fully realize their economic potential and further improve healthcare delivery systems, ongoing assessment and policy support are vital.